Frequência de enterobactérias produtoras de ß-Lactamases AmpC plasmidiais isoladas em infecção de corrente sangüínea - Campana, Eloiza Helena [UNIFESP] (2009)
The broad-spectrum cephalosporins are the main therapeutic options to Enterobacteriaceae infections and the resistance to these agents has been associated to ESβL production. However, plasmid-mediated AmpC β-lactamases (pAmpC) have been associated with this resistance phenotype. The aim of this study was to determine the occurrence of pAmpC among clinical isolates recovered from bloodstream from patients hospitalized at a Brazilian teaching hospital, collected between January and July 2006. A total of 133 non-repetitive Enterobacteriaceae per patients (65 K. pneumoniae, 41 E. coli, 18 P. mirabilis, 05 K. oxytoca and 04 Salmonella spp.) were studied. The antimicrobial susceptibility profile was determined by CLSI agar dilution method. ESβL phenotype was detected by doubledisk diffusion method while pAmpC production was evaluated by two phenotypic methods: modified three-dimensional and modified Hodge tests and the presence of pAmpC genes was confirmed by PCR and sequencing. Among tested antimicrobial, imipenem showed the highest susceptibility rate (99.2%), followed by cefoxitin (80.5%). K. pneumoniae presented high resistance to β-lactams. P. mirabilis isolates showed the lower susceptibility rate to ciprofloxacin (27.8%). Fifty-nine (44.4%) of studied isolates were phenotypically classified as ESβL producers. Modified threedimensional and Hodge methods classified 06 and 19 Enterobacteriaceae strains as pAmpC producers, respectively. Discordant results were observed between phenotypic pAmpC detection methods. Of those, a single K. pneumoniae isolate was confirmed as CMY-2 producer.